Primary Evaluation of Shape Recovery of Orthodontic Aligners Fabricated from Shape Memory Polymer (A Typodont Study) - Tarek M. Elshazly; Ludger Keilig; Yasmine Alkabani; Ahmed Ghoneima; Moosa Abuzayda; Sameh Talaat; Christoph P. Bourauel (MDPI AG, 2021)
As an innovative approach to overcome the rate-limiting staging of conventional aligners, using shape memory polymers (SMPs) as aligners' materials was investigated in this in vitro study. The ability of SMPs to shape recover and consequently move tooth, upon appropriate stimuli, was evaluated on a typodont model before clinical application. The study design was to achieve 1.9 mm correction movement of an upper central incisor by one aligner after multiple steps/activation. A custom-made aligned typodont model with a movable upper central incisor was scanned. Using an orthodontic software and a 3D printer, resin-models were generated. Seven aligners of ClearX sheets (SMPs) were fabricated by thermoforming on the resin aligned model. Each aligner was tested for repositioning of the central incisor in the typodont model. The model was scanned after each step and the corrective movement was measured through the superimposition of scans. Results showed that the total correction efficiency of the SMPs' aligner was ≈93% (1.76 mm). The corrective movement was 0.94 ± 0.04 mm after the reforming step, 0.66 ± 0.07 mm after the first activation step, and 0.15 ± 0.10 mm after the second activation step. It was concluded that aligners made of SMPs could have a promising future-use in orthodontic aesthetic treatment.